A evolução das políticas públicas no Brasil no período 1990-2020: o que elas garantem para pessoas com NEE e/ou deficiência? - Prado, Isabelli Tesser (2022)
Education is an institutionalized social practice, which the State has the duty to guarantee and promote its management. In this way, it is necessary to understand that it is part of a system – capitalism – and therefore undergoes changes according to the need to maintain this system, the economic and ideological interests of the ruling class. The changes that are promoted in the educational system occur through social policies, which have the function of organizing rights and duties of the subjects inserted there. Inclusion is part of these social promotion policies, aiming to alleviate inequalities, whether those arising from some type of disability, or due to the need for historical retraction, in order to make them actively part of society. However, the ways in which it occurs perversely include people with special educational needs, as it guarantees access and basic conditions in line with the law, but not effective permanence. That way, our objective is to analyze what was produced from public policies in the period from 1990 to 2020, in the Brazilian educational system at the federal level, in order to understand whether these regulations guarantee what is proposed in a more humanizing and inclusive education, as well as their intentions when actually applied. This work is intended to result not only in an analysis of these laws from a Marxist perspective, but also with the intention of producing a survey of legal formulations at the federal level for further consultation.